The Role of Baitus Shomad Grand Mosque in Tegalombo in Empowering the Community through the Management of Rest Areas and MSMEs - Andri Yulianto; Happy Agustiani (Manunggal Halim Jaya, 2026)
Mosques have strategic potential as centers of community-based economic empowerment; however, their utilization in strengthening Micro, Small, and Medium Enterprises (MSMEs) remains largely limited to socio-religious functions. This condition indicates a gap between the existing potential and the actual practice of mosque-based economic management. This study aims to analyze the community empowerment model developed by the Baitus Shomad Grand Mosque in Tegalombo through the management of a rest area and MSMEs, as well as its impact on the economic independence of the local community. This research employs a qualitative method with a case study approach. Data were collected through observation, in-depth interviews with mosque administrators and MSME actors, and documentation. Data validity was tested through source and method triangulation. The findings reveal that the mosque-based rest area is managed by providing business facilities, organizing vendor stalls, and offering continuous guidance to MSME actors. This model has proven effective in increasing local economic activities, expanding employment opportunities, and strengthening the business independence of the surrounding community. The study concludes that the integration of religious and economic functions through the optimization of mosque physical assets in the form of a rest area represents an effective, inclusive, and sustainable model of community empowerment. This model has the potential to be replicated in other mosques with similar characteristics.